POLA KOMUNIKASI ISLAM DALAM PEMBELAJARAN (Suatu Analisis Psikologi Pendidikan) - Authar, Tanzil; Warul Walidin; Syabuddin; Salami Mahmud (Anatesa : Kajian Pendidikan, Sosial dan Keagamaan, 2024)
The Quran does not specifically discuss Islamic communication practices. Islamic communication, typified by Qaulan, primarily revolves on interpersonal relationships. It involves linguistic interactions that are influenced by context and circumstances. The study employs qualitative methodologies. Research refers to the process of doing library research by analyzing material, such as written texts, notes, or reports, in order to provide novel research discoveries. Analytical terms are used to scrutinize information conveyed via symbols recorded in diverse media, including books, articles, and other mediums. The word "ill-defined" is used when the author is addressing a theory or notion that lacks a clear and precise definition, making it difficult to evaluate and develop into a comprehensible concept. The Qur'an comprises the verses known as Qaulan Karima, Qaulan Layyina, Qaulan Ma'rufa, Qaulan Sadida, Qaulan Baligha, and Qaulan Shakhila.